The Toynbee Affair at 100: The Birth of ‘World History’ and the Long Shadow of the Interwar Liberal Imaginaire - Arie M. Dubnov (Histories, 2023)
Functioning as “precedent” and “templates” for future transfers, the Greco-Turkish population exchange and the Lausanne Treaty) are undoubtedly events of world-historical significance. But they are also crucial in the genesis of the subfield of historical research we now call “World History”: they provided the backdrop against which Arnold Joseph Toynbee (1889–1975) began sketching his magnum opus, A Study of History and developed the foundations of this subfield of history writing. This article revisits the so-called “Toynbee Affair” and places it in its intellectual and political contexts. First, it revisits the British classicist scholarship that provided the backdrop and initial inspiration for Toynbee as it shifted its gaze from ancient Rome to Greece, which was put forward as a better model for foreign and imperial policy. Next, it examines Toynbee’s wartime activities and shows that his attitudes towards the new states of Central Europe were based on principles that often stood in tension with his activities and views connected to the Middle East. During these years, Toynbee was an active participant in a discourse concerning the need to manage “mixed populations,” which moved to the forefront of a new form of internationalism, while also exposed to the writings of authors such as Oswald Spengler and Frederick J. Teggart, who pushed him to advance a new type of historiography. Third, the article looks at the uneven reception of Toynbee’s ideas after 1945, including his views on the US, the “Muslim civilization,” and his controversial views on Jews and the politics of the Middle East. The article concludes by arguing that his views, which rested on a deep suspicion of liminal hybridity or cultural mestizos, failed to transcend the basic logic of separation developed in Lausanne. Entirely on the contrary: Toynbee’s story offers us a case in which we can recognize the making of the interwar “cultural imaginaire” and “reinvention of differences,” which continues shaping our view of “the West’s” supposed borders to this day.